Precise determination of stellar parameters of the ZZ Ceti and DAZ white dwarf GD 133 through asteroseismology. Issue 3 (20th April 2019) - Fu, J-N; Vauclair, G; Su, J; Fox Machado, L; Colas, F; Kim, S-L; Cang, T Q; Li, C; Niu, H B; Xue, H F; Li, Y; Jiang, X-J; et al.
ABSTRACT: An increasing number of white dwarf stars shows atmospheric chemical composition polluted by heavy elements accreted from debris disc material. The existence of such debris discs strongly suggests the presence of one or more planet(s) whose gravitational interaction with rocky planetesimals is responsible for their disruption by tidal effect. The ZZ Ceti pulsator and polluted DAZ white dwarf GD 133 are good candidates for searching such a potential planet. We started in 2011 a photometric follow-up of its pulsations. As a result of this work in progress, we used the data gathered from 2011 to 2015 to make an asteroseismological analysis of GD 133, providing the star parameters from the best-fitting model with M / M ⊙ = 0.630 ± 0.002, T eff = 12 400 ± 70 K, log( M He / M ) = −2.00 ± 0.02, log( M H / M ) = −4.50 ± 0.02, and determining a rotation period of ≈7 d.